Effect of sliding mating materials on vacuum tribological behaviors of sintered polycrystalline diamond. (January 2016) - Sha, Xiaohua; Yue, Wen; Zhao, Yihui; Lin, Fang; Wang, Chengbiao
Abstract: The comparative tribological behaviors of the sintered polycrystalline diamond (PCD) sliding against SiC, Si3 N4, GCr15 and Al2 O3 mating balls have been investigated by a ball-on-disk tribometer under vacuum conditions. Scanning electron microscope (SEM), energy dispersive X-ray spectrum (EDS) and Raman spectroscopy were performed to study the morphologies and chemical composition of the worn surfaces on the PCD and mating balls. The results showed that the coefficients of friction (COFs) of PCD/SiC and PCD/Si3 N4 tribopairs were about ten times as high as those of PCD/GCr15 and PCD/Al2 O3 tribopairs. The EDS and Raman spectroscopy results demonstrated that the higher friction and wear of PCD/SiC and PCD/Si3 N4 tribopairs were attributed to serious adhesion caused by the formation of C–C and Si–C bonds at the contact interface. Some diamond grains were found in the wear scar of GCr15 mating ball, which indicated that the embed diamond grains spalling from the PCD surface resulted in abrasive wear by plowing mechanism. Sliding against Al2 O3, the low ultimate surface roughness and chemical inertness maintained the super low COF and minimal wear of both the PCD disc and mating ball. These results proposed that the vacuum tribological behaviors of the PCD were significantly affected by mating materials. Highlights: The vacuum tribological behaviors of PCD against different mates were evaluated. The COFs of PCD/Al2 O3 and PCD/GCr15 are much lower than those of other tribopairs. The high COFs of PCD/SiC and PCD/Si3 N4 are attributed to the serious adhesion. Abrasive wear of PCD/GCr15 is due to embed diamond grains in mating ball. Low ultimate mate roughness leads to superior tribological behavior of PCD/Al2 O3 .